ANALISIS VEGETASI TUMBUHAN BAWAH DI SEKITAR TEGAKAN AREN (Arenga pinnata Merr) - Haidir Ali; Dina Naemah; Yusanto Nugroho (Universitas Lambung Mangkurat, 2022)
This research was intended to obtain the level of control of species based on the importance, namely the result of the relative density and relative frequency of all identified understorey species.The referred understorey is all types of plants in the form of grass, herbs, shrubs or low shrubs with a solitary life form, clumps, upright, creeping or climbing and being around plants or palm plants (A. pinnata Merr.). Sugar palm as it is known is a type of annual plant that reaches a height of 12 to 20 m, with a variety of benefits that can be used by the community ranging from leaves, stems, fruits and roots to provide business opportunities.The plot was determined by purposive sampling so that it represented the expected conditions and objectives with a distance of 10m between lines. The results showed that the Litu species (Lygodium scandens) is the most dominant understorey around the palm stands. The important value of Litu's understorey is 28.21%Penelitian ini dimaksudkan untuk mendapatkan tingkat penguasaan jenis berdasarkan nilai penting yaitu hasil dari kerapatan relatif dan frekuensi relative dari seluruh jenis tumbuhan bawah teridentifikasi. Tumbuhan bawah yang dimaksud merupakan seluruh jenis tanaman berupa rumput, herba, semak atau perdu rendah dengan bentuk hidup soliter, berumpun, tegak, menjalar atau memanjat dan berada disekitar tumbuhan atau tanaman aren (A. pinnata Merr.). Aren sebagaimana diketahui merupakan jenis tanaman tahunan yang mencapai tinggi 12 sampai 20 m, dengan beragam manfaat yang dapat digunakan oleh masyarakat mulai dari daun, batang, buah dan akar sehingga memberikan peluang usaha. Pembuatan plot ditentukan secara purposive sampling sehingga mewakili kondisi dan tujuan yang diharapkan dengan jarak antar jalur 10m. Hasil penelitian menunjukkan bahwa jenis Litu (Lygodium scandens adalah jenis tumbuhan bawah yang paling dominan berada disekitar tegakan aren. Nilai penting tumbuhan bawah Litu sebesar 28,21% dari 42 jenis tumbuhan bawah lainnya.